2021
DOI: 10.1007/s12602-021-09748-w
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Network and Meta-analysis on the Antiviral Mechanisms of Probiotics: A Preventive and Treatment Strategy to Mitigate SARS-CoV-2 Infection

Abstract: With the alarming rise of infected cases and deaths, COVID-19 is a pandemic, affecting 220 countries worldwide. Until now, no specific treatment is available against SARS-CoV-2. The causal virus SARS-CoV-2 primarily infects lung cells, leading to respiratory illness ranging in severity from the common cold to deadly pneumonia. This, with comorbidities, worsens the clinical outcome, particularly for immunosuppressed individuals with COVID-19. Interestingly, the commensal gut microbiota has been shown to improve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 85 publications
0
30
0
1
Order By: Relevance
“…The changing gut microbiota have been implicated in the change of the immune response, and thus might in part be associated with a greater morbidity and possibly mortality due to COVID-19. The support of the gut microbiota with probiotics could therefore improve the immunity and help fighting the SARS-CoV-2 infection [111]. The probiotics and prebiotics have been postulated to be beneficial in the frail older persons, however the conclusive evidence as regards the post COVID-19 older patients is still to be obtained [112].…”
Section: Covid-19-related Acute Sarcopeniatowards Prevention and Managementmentioning
confidence: 99%
“…The changing gut microbiota have been implicated in the change of the immune response, and thus might in part be associated with a greater morbidity and possibly mortality due to COVID-19. The support of the gut microbiota with probiotics could therefore improve the immunity and help fighting the SARS-CoV-2 infection [111]. The probiotics and prebiotics have been postulated to be beneficial in the frail older persons, however the conclusive evidence as regards the post COVID-19 older patients is still to be obtained [112].…”
Section: Covid-19-related Acute Sarcopeniatowards Prevention and Managementmentioning
confidence: 99%
“…They identified 90 genes potentially implicated in COVID-19 probiotics treatment. Moreover, the clearly shown that the application of probiotics could play a pivotal role on ACE2-mediated virus entry, activation of the systemic immune response, immunomodulatory pathways, lung tissue damage, cardiovascular complications, and altered metabolic pathways in the disease outcome (150). There are currently multiple lines of research with probiotics and numerous potential therapeutic indications, however studies with strong scientific evidence of therapeutic benefits are required.…”
Section: Treatment Proposals Prebiotics and Probioticsmentioning
confidence: 99%
“…Such alterations persist even after viral clearance and symptom recovery [38,39]. Samples of the bronchoalveolar lavage fluid from patients with COVID-19 and community-acquired pneumonia are dominated by bacteria that commonly exist in the oral cavity and upper respiratory tract [40]. In fact, the gut-lung axis has also been implicated in cytokine production that underlies COVID-19 severity and pulmonary damage [40,41].…”
Section: Gut Microbiome Disintegration Depletes Gut-derived Mk In Covid-19 Vulnerable Groupsmentioning
confidence: 99%
“…Its probiotic content may have implications for the prevention and treatment of COVID-19. A meta-analysis involving an association network concerning 90 identified training genes linked with COVID-19 and probiotic treatment reported that probiotics can therapeutically interfere with ACE2-mediated viral invasion, activation of the systemic immune response, Nlrp3-mediated immunomodulatory pathways, immune cell migration that cause pulmonary damage and cardiovascular difficulties, and altered glucose/lipid metabolic pathways in the disease prognosis [40].…”
Section: Fermented Milk Supplemented With Honey As a Source Of Probiotics And Bacterial Mkmentioning
confidence: 99%